Association between serum sodium level within normal range and handgrip strength in relation to hypertension status: a cross-sectional study - Yuji Shimizu (Nature Portfolio, 2021)
Abstract Serum sodium concentration within the normal range could act as an indicator of age-related changes such as decrease in muscle strength and impairment of capillary function. Since endothelial injury stimulates endothelial repair by enhancing CD34-positive cell production, the level of serum sodium may be inversely associated with that of circulating CD34-positive cells, thus indicating the degree of age-related endothelial injury. We conducted a cross-sectional study of 246 elderly Japanese men aged 60–69 years. Subjects were stratified by hypertension status because hypertension should act as a strong confounding factor for the analyses performed in this study. Serum sodium concentration was positively associated with handgrip strength in non-hypertensive subjects [standardized parameter estimate (β) = 0.29; p = 0.003], but not for hypertensive subjects (β = 0.01; p = 0.878), while it was inversely associated with circulating CD34-positive cell levels in non-hypertensive subjects [simple correlation coefficient (r) = − 0.28; p = 0.002] but not for hypertensive subjects (r = − 0.07; p = 0.454). For non-hypertensive elderly subjects, serum sodium concentration within the normal range is positively associated with handgrip strength and inversely associated with CD34-positive cells, thus partly indicating the degree of age-related endothelium injury. These associations could prove to be an efficient tool for clarifying the background mechanism governing the decrease in age-related muscle strength.